In vitro anthelmintic activity of psidium guajava hydroalcoholic extract against gastro-intestinal sheep nematodes - Silva, Luciana P.; Debiage, Rafael R.; Bronzel-Júnior, João L. [UNESP]; de Silva, Regildo M. G. [UNESP]; Mello-Peixoto, Erika C. T. (My University, 2020)
Tanniferous plants have been used for ruminants verminosis control and represent a possibility to minimize the pharmacological resistance against conventional antiparasitics. This study aimed to evaluate the antihelminthic activity of the hydroalcoholic extract of stem bark of guava tree (PgHA). It was performed the hatchability and larval migration inhibition assays to evaluate PgHA at the following concentrations 0.62, 1.25, 2.5 and 5.0 mg mL-1 and the control treatments. The total polyphenol, flavonoid and tannin contents were determined by phytochemical analysis, high performance liquid chromatography coupled to mass spectrometry. The antioxidant activity was evaluated by 1,1-diphenyl-2-picrylhydrazyl, ferric reducing antioxidant power and thiobarbituric acid reactive substances tests. It was also determinated total protein, intracellular H2 O2 and antioxidant activity of enzimes: glutathione S-transferase and superoxide dismutase. PgHA was able to inhibit both hatchability and larval migration, but only hatchability inhibition presented dose-dependent pattern. The antioxidant activity was demonstrated by linear regression with IC50 corresponding to 534.02 μg mL-1. The antiparasitic mechanism occurred through pro-oxidative activity by the increase of total proteins, intracellular H2 O2 and the lipid peroxidation products, as well as the increase of the enzymes above related. Thus, the PgHA showed antiparasitic activity in vitro.
Keywords: Gastrointestinal nematodes; Guava tree; Medicinal plants; Parasite; Tannins